Translational PK/PD and the first-in-human dose selection of a PD1/IL15: an engineered recombinant targeted cytokine for cancer immunotherapy - Yadav, Rajbharan; Schubbert, Suzanne; Holder, Patrick G.; Chiang, Eugene Y.; Kiabi, Nargess; Bogaert, Liz; Leung, Irene; Rashid, Rumana; Avery, Kendra N.; Bonzon, Christine; Desjarlais, John R.; Sanjabi, Shomyseh; et al. (Frontiers in Pharmacology, 2024)
Introduction: Interleukin 15 (IL-15) is a potential anticancer agent and numerous engineered IL-15 agonists are currently under clinical investigation. Selective targeting of IL-15 to specific lymphocytes may enhance therapeutic effects while helping to minimize toxicities.We designed and built a heterodimeric targeted cytokine (TaCk) that consists of an anti-programmed cell death 1 receptor antibody (anti-PD-1) and an engineered IL-15. This "PD1/IL15" selectively delivers IL-15 signaling to lymphocytes expressing PD-1. We then investigated the pharmacokinetic (PK) and pharmacodynamic (PD) effects of PD1/IL15 TaCk on immune cell subsets in cynomolgus monkeys after single and repeat intravenous dose administrations. We used these results to determine the first-in-human (FIH) dose and dosing frequency for early clinical trials.Results: The PD1/IL15 TaCk exhibited a nonlinear multiphasic PK profile, while the untargeted isotype control TaCk, containing an anti-respiratory syncytial virus antibody (RSV/IL15), showed linear and dose proportional PK. The PD1/IL15 TaCk also displayed a considerably prolonged PK (half-life range 1.0 to 4.1 days) compared to wild-type IL-15 (half-life 1.1 hours), which led to an enhanced cell expansion PD response. The PD was dose-dependent, durable, and selective for PD-1 + lymphocytes. Notably, the dose-and time-dependent PK was attributed to dynamic TMDD resulting from test article-induced lymphocyte expansion upon repeat administration. The recommended first-in-human (FIH) dose of PD1/IL15 TaCk is 0.003 mg/kg, determined based on a minimum anticipated biological effect level (MABEL) approach utilizing a combination of in vitro and preclinical in vivo data.This work provides insight into the complex PK/PD relationship of PD1/IL15 TaCk in monkeys and informs the recommended starting dose and dosing frequency selection to support clinical evaluation of this novel targeted cytokine.